Genome-wide association analysis provides insights into the genomics and extracellular expression of staphylococcus aureus proteases - Shuxian Li; William Monteith; Emily Rudolph; Samuel K Sheppard; Maisem Laabei (Virulence, 2025)
Extracellular proteases are a class of Staphylococcus aureus virulence factors that thwart the immune system, promote nutrient acquisition, and shape the activity of virulence determinants. S. aureus displays considerable phenotypic and genotypic variation within clinically important lineages, giving rise to diverse infection types. Therefore, understanding how protease expression influences pathogenicity requires consideration of the underlying genes and their regulation in natural populations. In this study we determined the protease activity of 134 USA300 S. aureus isolates from clinical infections and asymptomatic carriage. In high-throughput casein hydrolysis assays, bloodstream infection isolates had significantly lower protease activity than carriage isolates. To identify the genetic variation underlying this variation in protease expression, we employed a k-mer-based genome wide association study, identifying 68 genes with polymorphisms significantly associated with proteolytic activity. Population-scale genomic variation was compared with strains from a sequenced-defined transposon library, validating the function of 27 loci that were significantly associated with decreased protease expression. Associated genes included known protease-regulating genes, including agrA, but most were novel. These included genes linked to central metabolism, permeases, transporters and membrane proteins. Characterizing the complexity of protease regulation and expression will enhance our fundamental understanding of S. aureus virulence which may result in improved treatment options for problematic clinical S. aureus infections.